2018
DOI: 10.1186/s12889-018-5390-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and health outcomes among adolescents: the mediating role of traditional and cyber bullying victimization

Abstract: BackgroundIt is well-documented that obese children and adolescents tend to experience a variety of negative physical and psychological health consequences. Despite the association between obesity and physical and psychological well-being, few studies have examined the role of off-line and on-line forms of bullying victimization in this link. The main objective of the current study is to investigate the direct and mediating effects of traditional and cyber bullying victimization in explaining the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 91 publications
1
17
2
3
Order By: Relevance
“…31 32 The SUR model was employed because it assumes contemporaneous cross-equation error correlation,29 which is common among the set of linear regression equations used for mediation analyses. Previous epidemiological research has also adopted the SUR model for mediation analyses 33. The SUR model is also well suited for estimating and comparing indirect effects in independent variables with multiple categories (ie, housing affordability in quartiles).…”
Section: Methodsmentioning
confidence: 99%
“…31 32 The SUR model was employed because it assumes contemporaneous cross-equation error correlation,29 which is common among the set of linear regression equations used for mediation analyses. Previous epidemiological research has also adopted the SUR model for mediation analyses 33. The SUR model is also well suited for estimating and comparing indirect effects in independent variables with multiple categories (ie, housing affordability in quartiles).…”
Section: Methodsmentioning
confidence: 99%
“…However, studies about the role of weight and BMI in cyberbullying are still scarce. According to Lee et al (2018), overweight in childhood and adolescence is linked to several physical health and mental health problems but, also, to the likelihood of becoming a victim of bullying. In their study, authors found that BMI was related to physical and mental health problems and that victimization mediated the relationship between BMI and psychological symptoms in both traditional bulling and cyberbullying.…”
mentioning
confidence: 99%
“…Other studies often use binary measures (presence/absence) of bullying experiences or do not examine several different types of bullying, which may have different impacts (Kenny et al, 2018). The current sample was composed of a larger portion of adolescents with obesity (36.0%) compared to similar studies (Lee et al, 2018; Waasdorp et al, 2018), which enabled stratification by weight status.…”
Section: Discussionmentioning
confidence: 99%